Interval estimations for parameters of gompertz model with time-dependent covariate and right censored data - Kaveh Kiani,; Jayanthi Arasan,; Habshah Midi, (Universiti Kebangsaan Malaysia, 2012)
There are numerous parametric models for analyzing survival data such as exponential, Weibull, log-normal and gamma. One of such models is the Gompertz model which is widely used in biology and demography. Most of these models are extended to new forms for accommodating different types of censoring mechanisms and different types of covariates. In this paper the performance of the Gompertz model with time-dependent covariate in the presence of right censored data was studied. Moreover, the performance of the model was compared at different censoring proportions (CP) and sample sizes. Also, the model was compared with fixed covariate model. In addition, the effect of fitting a fixed covariate model wrongly to a data with time-dependent covariate was studied. Finally, two confidence interval estimation techniques, Wald and jackknife, were applied to the parameters of this model and the performance of the methods was compared.